Study of technology development prospects "intelligent energy systems" using distributed databases - Pavlenko, V.; Volianyk, O.; Ponomarenko, I.; Danylchenko, D. (Energy and Automation, 2025)
The study of energy systems in smart cities is becoming increasingly relevant in the context of global challenges related to climate change and the need to transition to sustainable energy. The growth of urbanization and the energy demand stimulate the search for innovative solutions to optimize energy consumption and reduce greenhouse gas emissions.The purpose of the research is to develop the concept of integrating technologies of distributed databases – "blockchain" and artificial intelligence into the energy systems of smart cities to achieve maximum efficiency, reliability, and sustainability.The research was conducted by analyzing the scientific literature, collecting and processing data on existing energy systems, and developing mathematical models to evaluate the effectiveness of the proposed solutions. Methods of statistical analysis, machine learning, and simulation modeling were used.As a result of the research, the structure of the energy system of a smart city was developed, which involves the integration of blockchain to ensure transparency and security of energy exchange, as well as artificial intelligence to optimize energy consumption and forecast demand. The proposed model proved to achieve significant economic efficiency and reduce carbon emissions. Prospects for further research consist in the development of detailed algorithms for various components of the system, as well as in conducting experimental studies on pilot projects.The integration of blockchain and artificial intelligence into the energy systems of smart cities is a promising direction for increasing their efficiency and sustainability. The proposed model allows for achieving significant energy savings and reducing greenhouse gas emissions. Further research should be directed to the development of specific algorithms and their testing in real conditions.Key words: smart city, energy system, blockchain, artificial intelligence, sustainable development, energy efficiency